Double Reading of Outsourced CT/MR Radiology Reports: Retrospective Analysis. Issue 8 (December 2021) - Vendrell, Jean-François; Frandon, Julien; Boussat, Bastien; Cotton, François; Ferretti, Gilbert; Sans, Nicolas; Tasu, Jean-Pierre; Beregi, Jean-Paul; Larbi, Ahmed
Abstract : Objectives: Our objective was to determine disagreement rates in radiological reports provided by using a double-reading protocol in a national teleradiology company. Methods: From January 2015 to July 2016, 134169 radiological exams from 36 French centers, benefited outsourced interpretations by certified radiologists, in both regular and after-hours activities. Of these, 2040 CT and MR-scans (1.5%) were subjected to a second opinion by other radiologists in the field of their anatomical specialty (cerebral, thoracic, abdominal-pelvic, and osteoarticular). A five-point agreement scale graded from 0 to 4 was assigned for each exam. Disagreements were considered as minor if no clinical consequence for patient (scores 1 and 2) and major if potential clinical consequence (score 3 and 4). Independent radiologists performed a retrospective analysis and a stratified statistical analysis. Results: Double reading was performed on CT-scans (n = 934/2040, 45.8%) and MR-scans (n = 1106/2040, 54.2%) performed in regular (80.1%) and after-hours activities (19.9%). Disagreement scores occurred in 437 exams (21.4%), including major disagreements in 59 (2.9%). Among these, 48/754 were assigned by the thoracic second reader (6.4%), 6/70 by the abdominal-pelvic second reader (8.6%), 3/901 by the osteoarticular second reader (0.3%), and 2/315 by the cerebral second reader (0.6%), with statistical significant difference. No additional disagreement rate was observed in regular and after-hours activities ( P = 0.63). Conclusions: Double-reading of outsourced CT and MRI interpretations yielded 21.4% disagreement rate, with potential clinical consequence for patient in 2, 9% of the cases. These results are in accordance with those previously reported and suggests that quality assurance of outsourced interpretations is needed.